The probiotic characteristics of Lactobacillus reuteri ZJ617 and its resistance to Escherichia coli O157:H7 challenge in HFD-fed mice - Yanfei Ma; Yingying Mao; Zhaoxi Deng; Shanshan Wang; Jingliang Liu; Haifeng Wang (Animal Nutriomics)
A high-fat diet (HFD) increases susceptibility to Escherichia coli colonization in the intestine and raises the risk of intestinal diseases. Lactobacillus reuteri, a commensal bacterium, plays a crucial role in regulating intestinal function and maintaining immune homeostasis. In this study, we aimed to evaluate the effects of L. reuteri on gut barrier function and systemic inflammation in HFD-fed mice challenged with Shiga toxin-producing E. coli O157:H7, and to further elucidate the potential protective mechanisms involved. The results show that supplementation of L. reuteri ZJ617 mitigates intestinal barrier impairment, inflammatory cell infiltration and systemic inflammation induced by E. coli O157:H7. The potential mechanisms of L. reuteri ZJ617 deal with it involving in forming biofilm, producing functional amino acids and various secondary metabolites. Our works provided comprehensively analysis of potential properties of L. reuteri ZJ617 and indicated that L. reuteri ZJ617 is a promising probiotic to prevent E. coli O157:H7 infection.